2018
DOI: 10.1007/s00414-018-1802-z
|View full text |Cite
|
Sign up to set email alerts
|

Forensic reconstruction of two military combat related shooting incidents using an anatomically correct synthetic skull with a surrogate skin/soft tissue layer

Abstract: Six synthetic head models wearing ballistic protective helmets were used to recreate two military combat-related shooting incidents (three per incident, designated 'Incident 1' and 'Incident 2'). Data on the events including engagement distances, weapon and ammunition types was collated by the Defence Science and Technology Laboratory. The models were shot with 7.62 × 39 mm ammunition downloaded to mean impact velocities of 581 m/s (SD 3.5 m/s) and 418 m/s (SD 8 m/s), respectively, to simulate the engagement d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…They do not come though without limitations. Whilst studies have shown that Synbone® exhibits a satisfactory reaction to impact as a cranial proxy [ 10 12 ] and can exhibit realistic reaction to ballistic injuries as demonstrated in the current study (e.g., hydraulic burst, Krönlein shot) there are still questions as to its suitability as a proxy for long bones [ 7 9 ]. Also, when ballistic testing on Synbone ® spheres used 7.62 × 39 mm ammunition at 50 m and 100 m the resulting injury patterns were considered to be “too comminuted and fragmented” when compared to contemporary military injuries encountered by participating physicians [ 12 ].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…They do not come though without limitations. Whilst studies have shown that Synbone® exhibits a satisfactory reaction to impact as a cranial proxy [ 10 12 ] and can exhibit realistic reaction to ballistic injuries as demonstrated in the current study (e.g., hydraulic burst, Krönlein shot) there are still questions as to its suitability as a proxy for long bones [ 7 9 ]. Also, when ballistic testing on Synbone ® spheres used 7.62 × 39 mm ammunition at 50 m and 100 m the resulting injury patterns were considered to be “too comminuted and fragmented” when compared to contemporary military injuries encountered by participating physicians [ 12 ].…”
Section: Discussionmentioning
confidence: 91%
“…This study aimed to expand upon the work done by Taylor and Kranioti [ 13 ], Smith et al [ 6 ] Thali et al [ 10 , 11 ], and Mahoney et al [ 7 , 14 ] on testing whether Synbone® spheres are good proxies for human crania in ballistic studies and to record different injury patterns observed at different distances. It was found that the entry points of the ammunition into the spheres exhibit similar morphological patterns to real forensic cases when shot from a distance less than 35 m while exit wounds were larger than documented forensic cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the sponge is not contained in anything resembling human tissue; thus, different types of bloodstains can also be deposited on the paper, which can impact the bloodstain pattern size and shape. Mahoney et al [11] published a method that observed back spatter on a synthetic skull; this methodology used ballistic gel and a surrogate skin layer to yield similar results that would be found in real-life situations. This study was used as an aid to develop the methodology to observe forward spatter as it implied the importance of using ballistic gel as a substitute for human tissue.…”
Section: Published Methods and Selection For Techniquementioning
confidence: 97%
“…Corpses or animals show several constraints, namely the ethical issue related to their use, the availability of specimens and the reproducibility of the results related to their heterogeneity [17,18]. Contrariwise, synthetic or non-humane biological materials showed a satisfactory to good level of reproducibility [5,18], in replacing human tissues like soft tissues (skin, muscle or brain tissue) or bones [1,14,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. For ballistics tests, these synthetic or non-humane biological materials are usually used in a combined way by assembling them together in order to create a realistic wound model.…”
Section: Shooting Tests In Wound Ballisticsmentioning
confidence: 99%